THE EMPOWERMENT OF VILLAGE YOUTH BY FACILITATOR THROUGH EDUCATIONAL TOURISM OF KAMPUNG DOLANAN SIDOWAYAH VILLAGE, POLANHARJO DISTRICT, KLATEN REGENCY - Wohangara, Maria Gorety Landu (Advances in Social Sciences Research Journal, 2019)
ABSTRACT This study aims to determine the process of empowering village youth through educational tourism in Kampung Dolanan. Educational tourism of Kampung Dolanan is aimed for for kindergarten and elementary school age children. In educational tourism there is a traditional game, Wayang, which is educational, and has a meaning of togetherness combined with outbond activity. With the existence of the tourism, village youth can be empowered. The determination of research subjects was conducted by purposive method, which consists of facilitators, namely Karang Taruna Desa (Village youth organization), Head of Village, Training 77 and empowered village youth. Data collection techniques were carried out using participatory observation, in-depth interviews, focus group discussions and documentation studies. The result of this research is that the empowerment process carried out by facilitators to village youth consisted of several stages. First, identifying potentials and opportunities. Second, compiling a group work plan based on the results of the research. Third, applying the activity plan. Fourth, monitoring the process of the results of activities, and fifth , evaluation. Keywords: educational tourism, facilitator, youth empowerment,